Formulation of an Antibacterial Peel-Off Gel Mask from Kombucha Fermented with Gerga Orange Peel Infusion (Citrus x aurantium L.) - Joevanda, Salsabila; Salsabilla, Navira; Qiftiah, Mariatul; Sani K, Fathnur; Sukmadani Rusdi, Mesa; Efendi, M. Rifqi (Indonesian Journal of Pharmaceutical Education, 2024)
Kombucha fermentation transforms complex organic compounds into beneficial substances such as polyphenols, vitamins, minerals, fiber, and probiotics. Gerga orange (Citrus x aurantium L.) peel, rich in bioactive compounds with antibacterial potential, is a promising substrate for kombucha fermentation. This study aimed to develop a fermented kombucha infusion from Gerga orange peel for use in an antibacterial peel-off gel mask and to assess the impact of hydroxypropyl methylcellulose (HPMC) concentrations (2%, 3%, and 4%) on the mask's properties. Extract preparation, organoleptic evaluation, total phenolic content (TPC) analysis, and gel mask formulation were conducted. Antibacterial activity was evaluated against Propionibacterium acnes using the well-diffusion method. Kombucha fermentation increased the TPC of Gerga orange peel infusion (26.53 mgGAE/g vs 25.77 mgGAE/g), imparted a fermentation aroma, and reduced pH from 4 to 2.7. HPMC concentration significantly influenced gel texture, spreadability, drying time, and pH, while color, aroma, and homogeneity remained unaffected. Antibacterial tests showed moderate activity for Formula 1 (2% HPMC; inhibition zone: 9.25 ± 0.35 mm). Stronger antibacterial effects were observed in Formulas 2 (3% HPMC; 13.93 ± 0.49 mm) and 3 (4% HPMC; 14.25 ± 0.71 mm). Kombucha fermentation of Gerga orange peel offers an innovative method for creating antibacterial gel masks. Higher HPMC concentrations improve antibacterial efficacy and physical properties, demonstrating potential against Propionibacterium acnes.